نماذج من "النجوم الشارقات" للنصوص العربية المؤسسة لعلم الميقات وأثرها على التقويم الزمني - قاسمي عمار (University of Eloued جامعة الوادي, 2024)
تهدف هذه الورقة البحثية إلى الوقوف على رسالة فريدة من نوعها لابن أبي الخير الحسني والموسومة: "النجوم الشارقات"، للكشف عن النصوص المكتوبة باللغة العربية، والتي تؤسس لعلم الميقات، كما تهدف إلى معرفة تأثير هذه النصوص وعلم الميقات عموما على التقويم الزمني وعلم الفلك المعاصر. وتتوقع أن تصل إلى النتيجة المركزية التالية: "علم الميقات هو علم السياق الزمني للأحداث ودلالتها ومصيرها من حيث الاتجاه النهائي لها، وفي القرآن الكريم مؤثرات كثيرة على هذا المعنى الذي ينفي مفهوم المصادفة العمياء ويجعل لحركة الأحداث وتقابلها واتجاهها ناظما إلهيا وموضعيا، فهو من العلوم المهمة لما فيه من فائدة؛ بمعرفة مدة السنين والشهور، والمواقيت وفصول الأزمان، وزيادة الليل والنهار ونقصانها، ومسير الكواكب وتبدل أشكالها ومراتب أفلاكها وسائر مناسباتها.. وكل ما يؤدي إلى إدامة الفكر وإمعان النظر في إثبات التوحيد ومعرفة كنه عظمة الخالق وسعة حكمته وجلال قدرته"، وعلاقة الكتاب المسطور بالكتاب المنثور والمنظور. This research paper aims to identify a unique treatise by Ibn Abi al-Khair al-Hasani, tagged: "The Shining Stars", to reveal texts written in Arabic, which establish the science of meekat, and to know the impact of these texts and the science of miqat in general on the chronological calendar and contemporary astronomy. "The science of miqat is the science of the temporal context of events, their significance and fate in terms of their final direction, and in the Holy Qur'an there are many influences on this meaning, which negates the concept of blind coincidence and makes the movement of events, their correspondence and direction a divine and topical regulator, as it is one of the important sciences because of its usefulness, knowing the duration of years and months, times and seasons of times, increasing and decreasing night and day, the course of the planets and the change of their shapes, the ranks of their orbits and all other occasions. And everything that leads to the perpetuation of thought and careful consideration in proving monotheism and knowing what it is the greatness of the Creator and the breadth of his wisdom and the majesty of his power", and the relationship of the written book with the scattered and visible book.
Keywords: علم الميقات؛ علم الفلك؛ التقويم الزمني؛ النظام المعرفي؛ السنن الكونية.